The Effect of Parenting Style, Self-Efficacy, and Self Regulated Learning on Adolescents’ Academic Achievement - Julia Theresya; Melly Latifah; Neti Hernawati (Journal of Child Development Studies, 2018)
Academic achievement as one of learning outcome indicator in adolescents influenced by the self and family environment factors. This study was aimed to analyze the effect of child characteristics, family characteristics, parenting style perceived by adolescents, self-efficacy and self regulated learning on adolescents academic achievement. The study used self report method which involved 91 eighth grade students from two junior high schools in Bogor. Data analysis included descriptive analysis and inference analysis (correlation test and linier regression test). Result showed that majority of samples perceived their parent as authoritative (86.8%) followed by authoritarian (11.0%) and permissive (2.2%). The result also showed that majority of samples had medium level in self-efficacy and self regulated learning. More than a half of samples had under average level in academic achievement. Correlation results showed that there were significant and positive relationship between authoritarian parenting style with birth order, family size as well as gender. Self regulated learning were significantly and positively related with authoritative parenting style (r=0.257, p-value<0.05) and self-efficacy (r=0.330, p-value<0.01). Meanwhile, regression results showed a positive effect of academic achievement on father's education (β=0.315, p-value=0.006) and authoritative parenting styles (β=0.259, p-value=0.014), as well as negatively on gender (β=-0.267, p-value=0.014) and permissive parenting style (β=-0.203, p-value=0.039).